Cystatin C as a predictor of mortality in elderly patients with chronic kidney disease. (2nd January 2019) - Bevc, Sebastjan; Hojs, Nina; Knehtl, Maša; Ekart, Robert; Hojs, Radovan
Abstract: Background: The prevalence of chronic kidney disease (CKD) in the elderly is high. Serum cystatin C is an accurate marker of kidney function and it also has prognostic utility in CKD patients. The aim of our study was to determine the prediction of serum cystatin C and other markers of kidney function on long-term survival in elderly CKD patients. Methods: Fifty eight adult Caucasian patients, older than 65 years, without known malignancy, thyroid disease and/or not on steroid therapy were enrolled in the study. In each patient, 51 CrEDTA clearance, serum creatinine, serum cystatin C, and estimated glomerular filtration rate using different equations were determined on the same day and patients were then followed for 11 years or until their death. Results: The means are as follows: 51 CrEDTA clearance 53.3 ± 17.4 ml/min/1.73 m 2, serum creatinine 1.62 ± 0.5 mg/dl, serum cystatin C 1.79 ± 0.5 mg/l, Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) creatinine equation 40.1 ± 14 ml/min/1.73 m 2, Berlin Initiative Study 2 (BIS2) equation 38.9 ± 10.7 ml/min/1.73 m 2, full age spectrum (FAS) creatinine equation 43.8 ± 13.8 ml/min/1.73 m 2, FAS cystatin C equation 40.1 ± 11.7 ml/min/1.73 m 2 . In the follow up period, 47 (81%) patients died. Cox regression analysis showed different hazard ratios (HRs) for death: for 51 CrEDTA clearance HR 1.022 (95% CI 1.004–1.042; p  = .015), serum creatinine HR 1.013 (95% CI 1.006–1.019; p  = .001), serum cystatin C HR 2.028 (95% CI 1.267–3.241; p  = .003), CKD-EPI creatinine equation HR 1.048 (95% CI 1.019–1.076; p  = .001), BIS2 equation HR 1.055 (95% CI 1.021–1.088; p  = .001), FAS creatinine equation HR 1.046 (95% CI 1.017–1.074; p  = .001), FAS cystatin C equation HR 1.039 (95% CI 1.010–1.071; p  = .009). Conclusions: Our results showed the highest HR for serum cystatin C among kidney function markers for prediction of outcome in elderly CKD patients.